2018
DOI: 10.1371/journal.pone.0196823
|View full text |Cite
|
Sign up to set email alerts
|

Studying the dynamics of interbeat interval time series of healthy and congestive heart failure subjects using scale based symbolic entropy analysis

Abstract: Considerable interest has been devoted for developing a deeper understanding of the dynamics of healthy biological systems and how these dynamics are affected due to aging and disease. Entropy based complexity measures have widely been used for quantifying the dynamics of physical and biological systems. These techniques have provided valuable information leading to a fuller understanding of the dynamics of these systems and underlying stimuli that are responsible for anomalous behavior. The single scale based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…The complex biological systems exhibit structures at multiple time scales and they function in a dynamic environment. The traditional approaches measure complexity at a single time scale and fail to account for multiple temporal scales inherent in the output signals of these systems [10,14]. In 2002, Costa et al proposed Multiscale Entropy (MSE), to represent heart rate dynamics at multiple time scales [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex biological systems exhibit structures at multiple time scales and they function in a dynamic environment. The traditional approaches measure complexity at a single time scale and fail to account for multiple temporal scales inherent in the output signals of these systems [10,14]. In 2002, Costa et al proposed Multiscale Entropy (MSE), to represent heart rate dynamics at multiple time scales [10].…”
Section: Introductionmentioning
confidence: 99%
“…Awan et al [14] proposed Multiscale Normalized Corrected Shannon Entropy (MNCSE) to study the dynamics of interbeat interval time series of healthy and diseased subjects. They compared the results of MNCSE with traditional MSE and found that MNCSE is more reliable and stable than MSE.…”
Section: Introductionmentioning
confidence: 99%
“…Their reported accuracy was 75.9% for the analysis of the RR interval time series and 85.6% for the differential RR interval time series. Awan et al [50] calculated MSE with scales from 1 to 20 and then utilized SVM, KNN, and random forest classifiers for discrimination, achieving testing accuracies of less than 85%. To the best of our knowledge, no study has reported a testing accuracy greater than 86% using MSE alone.…”
Section: Introductionmentioning
confidence: 99%
“…e previous studies [26][27][28] used last embedding dimension data points of PSR time series as the target set. Recently, the concept of multiple time scales has been introduced to study dynamics of healthy and pathological physiological systems such as regularity mechanism of cardiovascular system [29,30], postural control [31], and gait dynamics [32]. e APM mass concentrations are an outcome of complex natural and anthropogenic contributors evolving with time, which may operate on multiple time scales.…”
Section: Introductionmentioning
confidence: 99%